Nursing and spirituality - Pedrão,Raphael de Brito (2010)
ABSTRACT Objectives: To evaluate the spiritual well-being of nurses; to appraise their opinions as to the importance of offering patients spiritual assistance, and to verify whether nurses received any specific type of preparation during their professional training for giving spiritual assistance to patients. Methods: This is an exploratory and descriptive study, carried out with a sample of 30 nurses who worked at the Stepdown Unit and Oncology Unit of Hospital Israelita Albert Einstein, using the application of the Spiritual Well-Being Scale (SWS) and a questionnaire prepared by the authors. Results: On the Spiritual Well-Being Scale, 76.6% of nurses produced positive scores. On the Existential Well-Being subscale, 80% had positive scores, and on the Religious Well-Being subscale, 76.6% had positive scores. On the SWBS, the general average score was 107.26, and for the Existential and Religious ones, the average scores were 54.4 and 53.2, respectively. Most nurses responded affirmatively as to the importance of offering patients spiritual assistance, and 40% of nurses offered as rationale “to provide well-being and comfort to the patient”. Most nurses reported not having received professional training for giving spiritual assistance to patients in any of the nursing courses they had done. Conclusions: The results indicate the need for professional training and/or continued education courses in nursing to extend the reflection and discussion on spirituality and spiritual assistance to patients.